Odpowiedzi

2009-12-21T18:31:37+01:00
A) 3(x-1/2) + 2(y+3)=3 1/3
3x-1 /3 - y+3 / 2 = -1

3x-1,5+2y+6=3⅓
6x-2-3y+9=-1

3x+2y=-1,2 */3
6x-3y=-8 */2
9x+6y=-3,6
12x-6y=-16

x=-0,9

3x+2y=-1,2
3(-0,9)+2y=-1,2
y=0,75





b) x-3 / 4 - y+5/ 2 = -1,5
x-3 / 2 - 2y-7/ 3 = 1

2x-6-4y+20=-1,5
3x-9-4y-14=1

-2x+4y=15,5
3x-4y=24
x=39,5
3x-4y=24
3*(39,5)-4y=24
y=23,625



1 5 1
2009-12-21T18:47:41+01:00
A)
3x - 1,5 + 2y + 6 = 3 1/3
x - 1 - 1/2y + 3 = -1

3x + 2y = 3 1/3 + 1,5 - 6
x - 1/2y = -1 - 3 + 1

3x + 2y = -2
x - 1/2y = -3 / *(-3)

3x + 2y = -2
-3x + 1,5y = 9 (dodajemy)

3,5y = 7 / : 3,5
y = 2

3x + 2y = -2
y = 2

3x + 2*2 = -2
y = 2

3x + 4 = -2
y = 2

3x = - 2 - 4
y = 2

3x = -6 / 3
y = 2

x = - 2
y = 2

b)
x-3 (podzielić przez 4) - y+5 (podzielić przez dwa) = -1,5
x-3 (podzielić przez 3) - 2y-7 (podzielić przez trzy) = 1

1/4x - 3 - 1/2 y + 5 = - 1,5
1,2x - 3 - 2/3y - 7 = 1

1,4x - 1/2y = 1,5 + 3 - 5
1/2x - 2/3y = 1 + 3 + 7

1/4x - 1/2y = -3,5 / * (-2)
1/2x - 2/3y = 11

-1/2x + y = 7
1/2x - 2/3y = 11 (dodajemy)

1/3y = 18 / : 1/3
y = 54

-1/2x + y = 7
y = 54

-1/2x + 54 = 7
y = 54

-1/2x = 7 - 54
y = 54

-1/2x = -47 / : (-1/2)
y = 54

x = 94
y = 54